Merkel cell carcinoma: recent insights and new treatment options - Schrama, David; Ugurel, Selma; Becker, Jürgen C. (Current opinion in oncology, 2012)
Purpose of review: Merkel cell carcinoma (MCC) is a highly aggressive neuroendocrine carcinoma of the skin demonstrating a high propensity of recurrence and metastasis. Its 5-year disease-specific survival rate is only about 60%. Although MCC is still regarded as a very rare tumor entity, its incidence is rapidly increasing. In this regard, the American Cancer Society estimated almost 1500 new cases in the United States in 2008. Recent findings: The newly identified Merkel cell polyomavirus (MCV) has been found associated to most MCC cases. Nevertheless, the distinct molecular pathogenesis of MCC and its link to MCV is not yet fully understood. Moreover, the impact of MCV positivity on the course of disease and prognosis of MCC patients is controversially discussed. Summary: This review summarizes recent findings on MCC pathogenesis with a special emphasis on the impact of MCV, presents an overview of clinical aspects, and discusses treatment options.